2008
DOI: 10.1161/atvbaha.108.164715
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of ACE2 Enhances Plaque Stability in a Rabbit Model of Atherosclerosis

Abstract: Objective-The purpose of this study was to test the hypothesis that ACE2 overexpression may enhance atherosclerotic plaque stability by antagonizing ACE activity and converting angiotensin II to angiotensin 1-7. Methods and Results-Atherosclerotic plaques were induced in the abdominal aorta of 114 rabbits by endothelial injury and atherogenic diet. Gene therapy was performed in group A at week 4 and in group B at week 12, respectively. Each group of rabbits were randomly divided into 3 subgroups which received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
99
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(110 citation statements)
references
References 27 publications
10
99
0
1
Order By: Relevance
“…Our results revealed that rats in the no treatment group developed severe hyperglycemia, albuminuria and renal pathological changes as well as enhanced Ccr, which are characteristic of early diabetic nephropathy, and demonstrated that an animal model of diabetic nephropathy was successfully established. In our previous study (8) and the current study, the high expression of GFP in the Ad-GFP group and the high expression and activity of ACE2 in the Ad-ACE2 group, as well as the lack of noticeable side effects in these groups, indicated a high efficiency and safety of ACE2 gene transfer.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Our results revealed that rats in the no treatment group developed severe hyperglycemia, albuminuria and renal pathological changes as well as enhanced Ccr, which are characteristic of early diabetic nephropathy, and demonstrated that an animal model of diabetic nephropathy was successfully established. In our previous study (8) and the current study, the high expression of GFP in the Ad-GFP group and the high expression and activity of ACE2 in the Ad-ACE2 group, as well as the lack of noticeable side effects in these groups, indicated a high efficiency and safety of ACE2 gene transfer.…”
Section: Discussionsupporting
confidence: 69%
“…Recombinant adenoviruses (Ad) carrying the murine ACE2 (Ad-ACE2) or a control transgene EGFP (Ad-EGFP) were prepared with the AdMax system (Microbix Biosystems) using our previously described method (8).…”
Section: Preparation Of Ace2 Adenovirus Vectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of ACE2 in the pathophysiology of cardiovascular diseases is currently under intense investigation. The involvement of this enzyme in cardiac contractile function, hypertension, atherosclerosis and other cardiovascular diseases has recently been demonstrated (15)(16)(17). The present study offers evidence that ACE2 is involved in the hemostatic process and exhibits a protective action against thrombosis.…”
Section: Discussionsupporting
confidence: 57%
“…Recent studies have shown that the combination of an HMGCoA (3-hydroxy-3-methylglutaryl-coenzyme A) reductase inhibitor and an ARB has a better effect on relieving the severity of atherosclerosis and down-regulating the expression of lectin-like oxidized low density lipoprotein receptor-1 (LOX-1) than the use of a single drug [6] . Our previous study showed that angiotensin II plays an important role in the pathogenesis Combination of fluvastatin and losartan relieves atherosclerosis and macrophage infiltration in athero sclerotic plaques in rabbits 1260 www.nature.com/aps Yang YP et al Acta Pharmacologica Sinica npg of atherosclerosis [7,8] . In addition, Han et al and Koh et al also demonstrated that the combination of simvastatin and losartan has vascular protective effects [9,10] .…”
Section: Introductionmentioning
confidence: 99%